Quality Assurance In Higher Education In Algeria: Trends And Practices - Nassira KOURAICHE (Dirassat Journal Economic Issue, 2019)
The introduction of quality assurance (QA) in the field of higher education and scientific research in Algeria is very recent. The first structure responsible for the implementation of the quality assurance system was created in 2010. This study describes the steps taken to assess the level of implementation of this system. It shows that a significant number of measures have been taken among others the quality assurance cells (QAC), the development of a national reference (RNAQES)… The study recommends the reinforcement of awareness-raising actions, the development of tools and methods, the mobilization of teaching teams, the periodic evaluation and the operationalization of the structures involved in QA to fertilize quality practices in teaching. Superior. This study recommends sensibilization actions for the appropriation of the new reform, the tools and methods development, periodical evaluation and the operationalization of structures involved in the QA for introducing quality within the Congolese High and University Education.